2015
DOI: 10.1590/1807-55092015000400653
|View full text |Cite
|
Sign up to set email alerts
|

Como gênero e escolaridade interagem nos padrões de inatividade física em diferentes domínios em adultos?

Abstract: Rev Bras Educ Fís Esporte, (São Paulo) 2015 Out-Dez; 29(4):653-61 • 653Como gênero e escolaridade interagem nos padrões de inatividade física IntroduçãoComo gênero e escolaridade interagem nos padrões de inatividade física em diferentes domínios em adultos? CDD. 20.ed. 613.7 http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
(31 reference statements)
1
4
0
3
Order By: Relevance
“…Del Duca et al (32) conducted a study to analyze how gender and schooling interact in the PI patterns in adults; they found the lowest index of PA is related to the lower level of schooling, in which subjects presented only 5 to 8 years of complete studies. However, Souza et al (10) have shown in their studies the higher level of schooling, the PI lower.…”
Section: Discussionmentioning
confidence: 99%
“…Del Duca et al (32) conducted a study to analyze how gender and schooling interact in the PI patterns in adults; they found the lowest index of PA is related to the lower level of schooling, in which subjects presented only 5 to 8 years of complete studies. However, Souza et al (10) have shown in their studies the higher level of schooling, the PI lower.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, education is negatively associated with PA in the home environment (Costa et al, 2010 ; Nunes et al, 2015 ). As the education level is related to the socioeconomic level, it is believed that the most educated females have financial conditions that allow them to delegate their domestic activities to other people (Costa et al, 2010 ; Del Duca et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have explored each PA domain because a wide variation exists across countries with different income levels (Bauman et al, 2012 ; Del Duca et al, 2015 ), in addition to other determinants such as demographics and socioeconomic factors. For instance, active commuting and occupational PA may be more frequent in low- and middle-income countries, and as socioeconomic status improves, active transport decreases (Bauman et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…É caracterizado como o quarto fator de risco para a mortalidade global (6% de mortes em todo o mundo) e seus níveis têm aumentado progressivamente em muitos países, sobretudo pela urbanização, globalização e facilidades da vida moderna, que geram a redução do gasto energético para a realização das atividades de vida diária e no trabalho, resultando em comportamentos e ambientes insalubres, implicando na saúde geral dos indivíduos em todo o mundo (GUTHOLD et al, 2018;HASKELL et al, 2007;WHO, 2010, LEE et al, 2012HALLAL et al, 2012). No tocante às características socioeconômicas, de modo geral, identifica-se que a inatividade física no lazer é mais prevalente em mulheres e na população mais velha (GUTHOLD et al, 2018;NUNES et al, 2015;DEL DUCA et al, 2015;RHODES et al, 2017;MIELKE et al, 2015a;BRASIL, 2015, WHO, 2010. Além disso, foram registradas dessemelhanças nos níveis de AF entre indivíduos de diferentes níveis de escolaridade (MIELKE et al, 2015a;NUNES et al, 2015;DEL DUCA et al, 2015;MADEIRA et al, 2013;BRASIL, 2015).…”
Section: Lista De Abreviaturas E Siglasunclassified
“…No tocante às características socioeconômicas, de modo geral, identifica-se que a inatividade física no lazer é mais prevalente em mulheres e na população mais velha (GUTHOLD et al, 2018;NUNES et al, 2015;DEL DUCA et al, 2015;RHODES et al, 2017;MIELKE et al, 2015a;BRASIL, 2015, WHO, 2010. Além disso, foram registradas dessemelhanças nos níveis de AF entre indivíduos de diferentes níveis de escolaridade (MIELKE et al, 2015a;NUNES et al, 2015;DEL DUCA et al, 2015;MADEIRA et al, 2013;BRASIL, 2015).…”
Section: Lista De Abreviaturas E Siglasunclassified